Internalization of Clostridium perfringens α‐toxin leads to ERK activation and is involved on its cytotoxic effect - Monturiol‐Gross, Laura; Flores‐Díaz, Marietta; Campos‐Rodríguez, Diana; Mora, Rodrigo; Rodríguez‐Vega, Mariela; Marks, David L.; Alape‐Girón, Alberto (Cellular microbiology, 2014)
Summary Clostridium perfringens phospholipase C (CpPLC), also called α‐toxin, plays a key role in the pathogenesis of gas gangrene. CpPLC may lead to cell lysis at concentrations that cause extensive degradation of plasma membrane phospholipids. However, at sublytic concentrations it induces cytotoxicity without inducing evident membrane damage. The results of this work demonstrate that CpPLC becomes internalized in cells by a dynamin‐dependent mechanism and in a time progressive process: first, CpPLC colocalizes with caveolin both at the plasma membrane and in vesicles, and later it colocalizes with early and late endosomes and lysosomes. Lysosomal damage in the target cells is evident 9 h after CpPLC exposure. Our previous work demonstrated that CpPLCinduces ERK1/2 activation, which is involved in its cytotoxic effect. In this work we found that cholesterol sequestration, dynamin inhibition, as well as inhibition of actin polymerization, prevent CpPLC internalization and ERK1/2 activation, involving endocytosis in the signalling events required for CpPLC cytotoxic effect at sublytic concentrations. These results provide new insights about the mode of action of this bacterial phospholipase C, previously considered to act only locally on cell membrane.